Audit of Business: rather Consolidation than Rejection of Modern Range of Audit Services - Roman P. Bulyga (Учёт. Анализ. Аудит, 2019)
The article considers the concept of broad understanding of audit as a strategic direction in development of the audit profession in an information society. The author provides the definition of audit of business as a key notion of the concept, justifies the development of such new future directions of audit as audit of intellectual property, audit of business processes performance and strategic audit. The article classifies and lists characteristic features of the services rendered nowadays by audit firms comparing them with the components of audit of business which is regarded as an innovative direction of audit. A conclusion is made about a consolidating role of definitions of audit of business. The above role results in innovative directions opposite to the conventional range of audit services as a vector of their strategic consolidation.